2011
DOI: 10.1371/journal.pone.0024527
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Recruitment Manoeuvres Improve Lung Mechanics and Minimize Lung Injury during Mechanical Ventilation of Healthy Mice

Abstract: IntroductionMechanical ventilation (MV) of mice is increasingly required in experimental studies, but the conditions that allow stable ventilation of mice over several hours have not yet been fully defined. In addition, most previous studies documented vital parameters and lung mechanics only incompletely. The aim of the present study was to establish experimental conditions that keep these parameters within their physiological range over a period of 6 h. For this purpose, we also examined the effects of frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 60 publications
3
55
1
1
Order By: Relevance
“…These data fit with clinical studies which showed that RM had no effect on the level of systemic inflammatory cytokines in critically ill ventilated patients with and without ARDS [58,59]. Other experimental studies even showed a decreased inflammatory response when using RMs [60][61][62]. The cytokine attenuation during a RM could be due to the abolition of VILI as demonstrated by Kozian et al [63 •• ].…”
Section: Recruitment Maneuvers and The Open Lung Conceptsupporting
confidence: 83%
“…These data fit with clinical studies which showed that RM had no effect on the level of systemic inflammatory cytokines in critically ill ventilated patients with and without ARDS [58,59]. Other experimental studies even showed a decreased inflammatory response when using RMs [60][61][62]. The cytokine attenuation during a RM could be due to the abolition of VILI as demonstrated by Kozian et al [63 •• ].…”
Section: Recruitment Maneuvers and The Open Lung Conceptsupporting
confidence: 83%
“…Animals were investigated in LPS-induced and acid-induced models of ARDS, respectively, as well as cytokine-induced pulmonary inflammation, as described before (10,15). In brief, pulmonary inflammation was induced by intranasal (i.n.)…”
Section: Models and Analysis Of Ardsmentioning
confidence: 99%
“…Ventilation of Nrf2 2/2 and Nrf2 1/1 mice was performed with the flexiVent ventilator (SCIREQ, Montreal, Canada) as described (33) with pressure of 8 cm H 2 O and f = 180/min or 16 cm H 2 O and f = 80/min, FI O 2 = 0.3, and positive end-expiratory pressure = 2 cm H 2 O. Lung mechanics were followed by the forced oscillation technique.…”
Section: In Vivo Ventilationmentioning
confidence: 99%